2014
DOI: 10.1111/ejn.12781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of context‐drug learning on synaptic connectivity in the basolateral nucleus of the amygdala in rats

Abstract: Context-drug learning produces structural and functional synaptic changes in the circuitry of the basolateral nucleus of the amygdala (BLA). However, how the synaptic changes translated to the neuronal targets was not established. Thus, in the present study, immunohistochemistry with a cell specific marker and the stereological quantification of synapses was used to determine if context-drug learning increases the number of excitatory and inhibitory/modulatory synapses contacting the gamma-aminobutyric acid (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…S8(B, C)). As previously described [ 110 , 111 ] and in accord with well recognized criteria [ 112 ], a synapse was identified by the presence of presynaptic neurotransmitter vesicles and a synaptic cleft with parallel, electron dense, thickened pre- and postsynaptic membranes and the presence of electron dense content in the synaptic cleft. Consistent with the report that greater than 90% of the dopaminergic synapses in the human striatum are symmetric [ 113 ] and are functionally inhibitory or modulatory, all of the synapses observed were symmetric synapses (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…S8(B, C)). As previously described [ 110 , 111 ] and in accord with well recognized criteria [ 112 ], a synapse was identified by the presence of presynaptic neurotransmitter vesicles and a synaptic cleft with parallel, electron dense, thickened pre- and postsynaptic membranes and the presence of electron dense content in the synaptic cleft. Consistent with the report that greater than 90% of the dopaminergic synapses in the human striatum are symmetric [ 113 ] and are functionally inhibitory or modulatory, all of the synapses observed were symmetric synapses (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Increased BLA activity is a characteristic of some rat models of addiction (Rademacher et al, 2015) and results in insensitivity to reward devaluation (Wassum and Izquierdo, 2015). Insensitivity to reward devaluation is also triggered by stress, however, certain stressors can also result in the enhancement of the motivation for reward (Sharp, 2017).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Indeed, the long-lasting effect of chronic cocaine exposure to produce insensitivity to reward devaluation has been suggested to rely on a persistent, off-drug alteration in BLA signaling (Schoenbaum and Setlow, 2005). Using immunohistochemical and stereological analysis, it was recently found that amphetamine conditioned place preference experience alters synaptic connectivity within the BLA network through its GABA interneurons, resulting in long-lasting effects on BLA signaling (Rademacher et al, 2015). After 30 days of withdrawal from cocaine, the proportion of BLA delay-dependent anticipatory neurons is reduced.…”
Section: Bla In Addictionmentioning
confidence: 99%